MORPHOMETRIC CHARACTERIZATION AND THE FIRST TAXONOMIC SYNTHESIS OF TERRESTRIAL CYANOBACTERIA FROM THE ATLANTIC FOREST IN NORTHEASTERN BRAZIL - Ribeiro Da Anunciação, Raylane; Paulino, Jonatas M.; Moura, Ariadne N.; Laughinghouse Iv, H. Dail; Gama, Watson A. (Phytotaxa, 2024)
Cyanobacteria are very morphological diverse and the taxonomic inventories are the basis of the knowledge about their biodiversity. However, these studies have decreased in the last years, mainly due to advances in molecular techniques, evenness these tools have their limitations, like sequence libraries. In order to reveal the importance of taxonomic inventories to little known organisms and unexplored areas, the present study was carried out with terrestrial cyanobacteria from the Atlantic Forest of northeastern Brazil, compared to results with the state of the art of this group in the country. A total of 60 infrageneric taxa were found and 62.8% of identified species were new records to northeastern Brazil. Most of the previous studies were performed in the state of São Paulo (>70%) and half of the country has no records of terrestrial cyanobacteria due to the lack of studies. Thus, taxonomic surveys are still important to understand the cyanobacterial distribution and to characterize rare taxa and the biodiversity from unstudied areas and habitats.